Redefining Myeloid Cell Subsets in Murine Spleen - Hey, Ying-Ying; Tan, Jonathan K. H.; O’Neill, Helen C. (Frontiers in Immunology, 2016)
Spleen is known to contain multiple dendritic and myeloid cell subsets, distinguishable on the basis of phenotype, function and anatomical location. As a result of recent intensive flow cytometric analyses, splenic DC subsets are now better characterized than other myeloid subsets. In order to identify and fully characterize a novel splenic subset termed ‘L-DC’ in relation to other myeloid cells, it was necessary to investigate myeloid subsets in more detail. In terms of cell surface phenotype, L-DC were initially characterized as a CD11bhiCD11cloMHCII-Ly6C-Ly6G- subset in murine spleen. Their expression of CD43, lack of MHCII, and a low level of CD11c was shown to best differentiate L-DC by phenotype from conventional DC subsets. A complete analysis of all subsets in spleen led to the classification of CD11bhiCD11cloMHCII-Ly6CloLy6G- cells as monocytes, expressing CX3CR1, CD43 and CD115. Siglec-F expression was used to identify a specific eosinophil population, distinguishable from both Ly6Clo and Ly6Chi monocytes and other DC subsets. L-DC were characterized as a clear subset of CD11bhiCD11cloMHCII-Ly6C-Ly6G- cells which are CD43+, Siglec-F- and CD115-. Changes in the prevalence of L-DC compared to other subsets in spleens of mutant mice confirmed the phenotypic distinction between L-DC, cDC and monocyte subsets. L-DC development in vivo was shown to occur independently of the BATF3 transcription factor that regulates cDC development, and also independently of the FLT3L and GM-CSF growth factors which drive cDC and monocyte development, so distinguishing L-DC from these commonly defined cell types.